Psychoeducation to prevent bullying of teenagers in the Jember Muhammadiyah Student Association community - Nurul Izza Pratiwi; Yuni Nur Hamida (Yayasan Adra Karima Hubbi, 2024)
Adolescents have self-control patterns that still tend to be difficult in their development, so they are vulnerable to experiencing and committing violence in their social interactions. The violence in question can be any form of action such as bullying, emotional, psychological, physical or sexual violence experienced by teenagers. The findings of the problem of bullying in the form of violence also occurred among Muhammadiyah school students in Jember district. This problem of violence involves all elements starting from peers, teachers, parents, the school environment and the home environment. The IPM Jember community, which is an agent of change in the school environment, needs more in-depth education regarding the issue of youth violence through providing psychoeducation. The aim of the psychoeducation program is to increase IPM Jember students' awareness and knowledge about violence against teenagers. This research uses a quantitative experimental approach with a quasi-experimental type of experiment. The research design used is a pre-post test which will be given before and after intervention treatment in the form of psychoeducation. The subjects used in this research were 18 IPM Jember community administrators with samples taken using a purposive sampling technique. Data analysis used a paired t test which was used to compare the average measurements before and after the intervention was given. The research results based on the paired samples test have a significance value (2-tailed) of 0.000 < 0.05, indicating that there is a significant difference between the pre-test variables and the post-test variables. This indicates that the intervention or psychoeducation provided is effective in improving outcomes.